Assessing the Vernacular Knowledge and Financial Business Models Innovations of Shepherding Entrepreneurs in Swat - Muhammad Ishaq; Dr. Gul Ghutai; Dr. Muhammad Tariq (Indus Journal of Social Sciences, 2025)
The study aims to assess the vernacular business model sustainability approaches used by the agropastoral shepherds for earning a sustainable livelihood in district Swat. These small-scale entrepreneurs inhibit the issues of metabolic rift and contribute to economic well-being of the residents, although not without exhibiting rent seeking behaviour by way of consuming common natural resources. The study uses a Big Q qualitative research approach with thematic analysis done for data collected through semi-structured interviews done with 12 participants of the study. The findings of the study entails that these people living at the bottom of pyramid most of the time work for their landlords from upper regions of Swat. Due to economic exigencies, they rely on Kameetis for their financial sustainability. There is a decline in the homesteading practices by these people due to the fact that they are mobile in nature. Despite their advantages they lack access to quality animal care and often seen as vectors of zoonotic diseases in target area of study. Their income is variable due to economic fluctuations and their operations are unbanked which does not augur well with formal banking operations during the Eid- Azha season of the year. The study concludes that shepherd use vernacular indigenous knowledge to manage their business models and willing to undertake formalization of their practices which will not only enhance the financial sustainability but also enhance productivity in terms of meat, leather, wool sectors of economy Thus, contributing to the improvements in public health and food security. The contributes to broader discussions regarding the preservations of centuries old vernacular knowledge of shepherding but also proposes a simple yet magnanimous framework for inclusion of these shepherds in the formal economy through pathways supported by policy interventions.